Relationships between NDVI and visual quality in cool-season turfgrass: II. Factors affecting NDVI and its component reflectances. - Bremer, Dale J.; Lee, Hyeonju; Su, Kemin; Keeley, Steven J. (My University, 2011)
Normalized difference vegetation index (NDVI, computed as [near infrared (NIR) – Red)]/[NIR + Red]) may provide an objective means to evaluate visual quality of turfgrass. The NDVI is influenced by red (visible) and NIR reflectance (invisible), but each may respond differently to environmental factors; basic information is lacking about the two components in relation to turf quality. In this 3-yr study near Manhattan, KS, we examined relationships of NDVI and its component reflectances along with visual quality ratings in Kentucky bluegrass (Poa pratensis L., ‘Apollo’), two Kentucky bluegrass × Texas bluegrass (Poa arachnifera Torr.) hybrids (‘Thermal Blue’ and ‘Reveille’), and tall fescue (Festuca arundinacea Schreb., ‘Dynasty’). Percentage green cover was measured with digital image analysis and shoot density was estimated visually to evaluate their impacts on turf quality and reflectance. Differences in NDVI and red and NIR reflectances were observed among turfgrasses at each level of quality. Across the range of turf quality, NDVI was influenced more strongly by red than NIR reflectance. Red reflectance was strongly affected by density (r = 0.85) and green cover (r = 0.86); NIR reflectance was affected by density (r = 0.63) but negligibly by green cover. Results suggest other fundamental factors that are poorly understood may be affecting NIR reflectance and, hence, NDVI in turf. These factors may confound relationships between NDVI and turf quality and require further study.
Keywords: Normalized difference vegetation index; Turfgrass; NIR reflectance; Red reflectance; Turf quality